PEMANFAATAN ALOKASI DANA DESA TERHADAP PEMBERDAYAAN MASYARAKAT DAN KELEMBAGAAN DESA - Ishak, Muhammad; Hasan, Adnan (Bongaya Journal of Research in Accounting (BJRA), 2020)
This study aims to help resolve the problems contained in the management of the Village Fund Allocation (ADD), so that issues regarding the management of the Village Fund Allocation (ADD) can prove and explain the strategic plans and objectives that have been planned and established by government organizations run according to planning or initial objectives effectively and efficiently. This study shows that the system for utilizing village fund allocations in community empowerment, there are four empowerment activities that are realized, such as management of public health services, education and culture, community empowerment cadres, and community empowerment cadre training. The system of utilizing the allocation of village funds in village institutions there are four institutional activities that have been realized such as the organization of peace and order, fostering religious harmony, fostering Empowerment of Family Welfare and dasawisma, and fostering the institution of youth organizations.